ANALYSIS OF THE GENESIS AND FORMATION OF THE PHILOSOPHY OF LANGUAGE - K. Zh. Turemuratova,; Seitakhmetova N.L., (Academic Journal of Physical and Chemical Sciences, 2020)
The philosophy of language is the important research area of the philosophy, which identifies the fundamental role of the language and speech in the cognition and the structures of the consciousness and knowledge. The philosophy of the language is one of the central areas of the research in modern western philosophy, which focuses on the concept of the language as the key of understanding the knowledge. The predecessors of the philosophical and linguistic direction were Aristotle (the treatise “Categories”), I. Kant (the development of the categories of the mind), J.J. Rousseau (ideas about the origin of writing), J. Mill (contribution to the theory of the reference), V. Humboldt, and others. The transition from the philosophical classics to the period of the philosophy of the language is associated with the change in the object of research: instead of “ideas” came linguistic entities “sentences” and “terms”. The cognizing subject often shifts to the periphery of the cognitive process or eliminated altogether. At the same time, the so-called “linguistic turn” is characteristic of an extremely wide range of the modern lines of the philosophy development, including phenomenology and hermeneutics, structuralism and post structuralism. Modern philosophy considers it problematic in the principle to distract from the linguistic aspect of the philosophical problems